Study of risk factors in progression of chronic kidney disease (CKD) - Vernekar, Ritesh; Dharmani, Sunil; Prabha, Vikram (International Multidisciplinary Research Journal, 2013)
Chronic kidney disease is a growing epidemic, with at least 10 million people with kidney damage. Diabetic kidney disease is the most common cause of ESRD worldwide. The rate of decline of GFR is variable, especially in diabetics, ranging from 2 to 20 ml/min/1.73 m2/yr. The reasons for these differences in the rate of disease progression are multifactorial, including both non-modifiable and modifiable factors. Aim is to retard progression of disease as cost of therapy is high. The study was planned to identify progression factors.